Cardio-renal-metabolic laboratory profile: an integrated strategy for the prevention and management of chronic non-communicable diseases - Figueroa Montes, Luis Edgardo (2025)
Objective: This article emphasizes the need to integrate cardiovascular, renal, and metabolic assessments into routine clinical practice, with the aim of improving the prevention, diagnosis, and management of chronic noncommunicable diseases (NCDs). Methods: We conducted a comprehensive review of the current medical literature on cardio-renal-metabolic syndrome, alongside a critical analysis of traditional clinical profiles. Based on these findings, we propose a novel integrated laboratory profile that captures the interconnections between these systems, aiming to enhance diagnostic accuracy and patient management. Results: Significant gaps in current fragmented assessments were identified, leading to the development of a profile that integrates key biomarkers from all three systems for a more comprehensive and accurate evaluation. This profile will be implemented according to the complexity of the care levels and according to the patient’s stage of cardio-renalmetabolic syndrome. Conclusion: Implementation of the new integrated cardiorenal-metabolic profile could likely optimize clinical care, reduce healthcare costs, and improve patient outcomes. However, its success will depend on the technical and logistical capabilities of clinical laboratory networks, as well as the stage of the patient’s disease and the level of care at which it is implemented.